(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Root crops such as carrots, potatoes, turnips, sweet potatoes, beetroot, cassava, and sugar beets are utilized in various food industries for producing flour, chips, snacks, confectionery, vegetable oils, starch-syrups, beer, and alcohol. Root crops are also used as raw materials for producing compound feed products and as tasty additives for livestock. Carrot root, for instance, contains 9-10 % starch, 4-6 % fiber, 65-70 % carbohydrates, and 14 % vitamins. Sugar beet, a root crop, is highly valued for its starch and carbohydrate content, serving as a palatable addition to animal diets. Sugar beet root consists of 73.6 % carbohydrates, 10.8 % starch, 2.2 % fiber, 1.8 % ash, and 12 % water. Root crops play a significant role in increasing the starch content of compound feed products due to their high starch content and palatability. Root crops typically contain 24-28 % starch, 46-50 % carbohydrates, 2-4 % fiber, 8 % lysine, and 7 % arginine.